2014
DOI: 10.1155/2014/653239
|View full text |Cite|
|
Sign up to set email alerts
|

Reference Values of Pulse Wave Velocity in Healthy People from an Urban and Rural Argentinean Population

Abstract: In medical practice the reference values of arterial stiffness came from multicenter registries obtained in Asia, USA, Australia and Europe. Pulse wave velocity (PWV) is the gold standard method for arterial stiffness quantification; however, in South America, there are few population-based studies. In this research PWV was measured in healthy asymptomatic and normotensive subjects without history of hypertension in first-degree relatives. Normal PWV and the 95% confidence intervals values were obtained in 780… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
56
7
7

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 31 publications
(42 reference statements)
9
56
7
7
Order By: Relevance
“…Nonetheless, we must consider that similarities in several demographic and socio‐cultural aspects in the general population of Argentina are present. The prevalence of hypertension reported in this study in a rural area is comparable to that reported in epidemiological population‐based studies in our country …”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Nonetheless, we must consider that similarities in several demographic and socio‐cultural aspects in the general population of Argentina are present. The prevalence of hypertension reported in this study in a rural area is comparable to that reported in epidemiological population‐based studies in our country …”
Section: Discussionsupporting
confidence: 76%
“…This epidemiological study is a part of a project that started in 2010 in Tandil, Buenos Aires Province, aimed at investigating the prevalence of CV risk factors in a well‐characterized population. Preliminary results have been recently reported . This work is a descriptive case‐control, observational, and cross‐sectional population‐based study and was divided into 2 well‐differentiated analysis: (1) the quantification of normal values of PWV corresponding to each decade of age in a normotensive population of normotensive parents, and (2) to investigate the effects of isolated arterial hypertension on PWV in non‐treated patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 However, reductions in cSBP and PWV have the potential to reduce the risk of additional cardiovascular events, then reinforcing the potential benefit of regular physical activity. 5 Our study identified a strong positive correlation between PWV and age, as did studies that determined reference values, 13,22 evaluated and compared competitive athletes and active individuals, 23 and a study in men engaging in moderate exercise using a cycle ergometer. 24 Other factors may be associated with PWV, such as BP and the intensity of exercise 12 and body weight.…”
Section: Discussionmentioning
confidence: 82%
“…The carotid‐femoral PWV is the most tested noninvasive method to measure arterial stiffness because of its simplicity, accuracy, and reproducibility Artery stiffness of the large arteries is mostly dependent on the content and organization of elastic fibers of the vascular wall A stiffer arterial tree leads to increased cardiac afterload and energy expenditure in the systolic work Despite being an independent predictor of cardiovascular morbidity and mortality, the use of PWV in clinical settings depends on the existence of reference values for different groups of patients. Studies to determine reference values of PWV and the identification of its main determinants have mostly been performed in adults Some studies on this subject have also conducted in children and adolescents However, most investigations studied Caucasians or black populations living out of Africa. To the best of our knowledge, this is the first study aimed to define reference values of PWV in prepubertal and healthy children in Africa.…”
Section: Discussionmentioning
confidence: 99%